A trajectory optimization method for UAV cascade relay broadcast communication system - LI Dongxia; SONG Siyu; LIU Haitao (Xibei Gongye Daxue Xuebao, 2023)
An unmanned aerial vehicle's(UAV) trajectory optimization is an important way to improve the performance of its relay communication system. The trajectory optimization method for the UAV cascade relay broadcast communication system that uses the decoding and forwarding protocols is studied. Firstly, the expressions of the signal-to-noise ratio of the UAV and the user are given. Then, a joint trajectory optimization method and a distributed trajectory optimization method for cascaded UAVs based on the minimized maximum user interruption probability are proposed. The transmission performance of the system link that uses the two trajectory optimization methods is studied; the mathematical expressions of the relay communication system's traverse capacity and the outage probability of a single user are given. Finally, the influence of the relay communication system's characteristic parameters on the optimal trajectory of the cascade relay UAV and its performance are verified with computer simulations. The simulation results show that the performance of the two trajectory optimization methods is basically the same, thus verifying the effectiveness of the trajectory optimization criterion.